A review on the evolution and characteristics of post-mortem imaging techniques. (December 2020) - Varela Morillas, Álvaro; Nurgaliyeva, Zhanna; Gooch, James; Frascione, Nunzianda
Highlights: Traditional autopsy presents some limitations in time, cost and physical resources. New post-mortem imaging techniques have been in development since the early 70s. A review of the history and development of these techniques shed some light in their advantages and disadvantages. These novel techniques are a the very least as sensitive as traditional autopsy. At the current state these techniques can be at least used in combination with traditional techniques for more accurate information Abstract: Up until the beginning of the 21 st century, the technique of choice for the forensic medical examination of a deceased individual was the traditional medical autopsy. This, however, has begun to change with the introduction of post-mortem imaging. Post-mortem imaging, or 'virtual autopsy', is a novel area of radiology that utilises non-invasive imaging techniques for the examination of a body. Many of the techniques used to conduct a virtual autopsy are more commonly employed within clinical diagnostic, such as computed tomography or magnetic resonance imaging. In recent years, post-mortem imaging has gathered significant momentum as a robust and objective methodology capable of compiling relevant intelligence without disturbing a body. This review identifies and describes the techniques currently available for post-mortem imaging and provides an insight on their advantages and disadvantages compared to traditional autopsy methods. The aim of this paper is to highlight the most relevant milestones accomplished in this field and the potential application of this technique within current forensic frameworks.